A Base Nacional Comum Curricular no contexto da rede municipal de ensino de São Luís/MA: implicações no currículo escolar sob a visão dos professores - PEDROZO, Nelcyleide de Jesus (2024)
This research deals with the implications of the National Common Curricular Base (BNCC) in the school curriculum of the municipal education network of São Luís/MA. Since its approval in December 2017, the BNCC has become a mandatory reference in the preparation of curricula for states and municipalities. However, this research was based on the following questions: Are the curricula of municipal schools in São Luís/MA based on BNCC determinations? How do teachers in the municipal network of São Luís/MA perceive or experience the construction of the school curriculum? What are the challenges they face in implementing BNCC at school? Therefore, to answer these questions, the present research has as its general objective, to analyze the implications of the BNCC in the school curriculum of the municipal education network of São Luís/MA, from the teachers' point of view. And as specific objectives, discuss the context of construction of the BNCC, its relationships and developments in the construction of the school curriculum in the municipal education network of São Luís/MA; identify the strategies adopted in the municipality of São Luís/MA to enable the implementation of the BNCC in municipal schools; analyze the curricula of the schools investigated, in their content and organizational processes, understanding the implications of the BNCC in these curricula. Therefore, this is a qualitative research approach, involving bibliographic, documentary and field studies, based on the Historical-Dialectical Materialism (MHD) method. Therefore, we articulate among the categories of (MHD) the dimensions of historicization, singularity, particularity, totality, mediation and contradiction. The theoretical framework consists of contributions from authors such as: Apple (2011), Arroyo (2013), Dourado (2010), Freitas (2018), Macedo (2018, 2019), Michael Young (2014), Sacristán (2013), Saviani (2008; 2020; 2021) Silva (2015), among others. For data collection, the questionnaire was used as instruments, aiming to gather the profile of the 17 (seventeen) research subjects from the two schools investigated, one from the Urban Zone - Center Center and the other from the Rural Zone and the semi-structured interview which allowed greater freedom for the participants to inquire. The collected data were analyzed using Bardin's Content Analysis Technique (1977). The main results found showed that the BNCC was decisive in the construction of the curriculum of the Municipal Education Network of São Luís, bringing implications for the development of the curriculum, such as: The need to compensate for the curriculum design, present in the teachers' positioning. The understanding on the part of teachers that the curriculum has a direct relationship with teacher practice. Some teachers are still unaware of the curriculum document prepared for the São Luís education network and the DCTM, since not everyone participated or was involved in the preparation of the aforementioned documents. There was also a significant dependence of teachers on the textbook, seen as guidance for teaching practice. It was also identified that teachers conduct their practices in a way of constant flexibility so that they can meet what is determined by the BNCC and the specificities of student learning and the reality of each school and this constitutes one of the challenges, especially after the post-pandemic context combined with the lack of continued training and adequate physical infrastructure and resources.